Application of 3D-printed anthropomorphic head phantom for quality assurance of 3D-conformal radiation therapy - Jalalludin, Nur Asilah (2020)
Aim and Objectives: This study evaluated the application of 3D-printed anthropomorphic head phantom for dosimetric verification. Materials and methods: Using head region of a RANDO phantom as a substitute for an actual patient, a custom head phantom was constructed using a 3D printer, with printing material of polylactic acid filament. The RANDO head phantom and the 3D-printed head phantom were used to compare the calculated and measured doses. Results: When the RANDO head phantom was used to compare the calculated and measured dose, the gamma passing rate for γ ≤ 1 was 85.1 %. When the 3D-printed head phantom was used, the gamma passing rate for γ ≤ 1 was 46.6 %. Conclusion: It was determined that the use of 3D-printed phantom for dosimetric verification is less feasible. Efforts must be made for improvements or further refinement of the phantom construction process is needed for clinical use.